2004
DOI: 10.1097/01.inf.0000141722.10130.50
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of RIX4414 Live Attenuated Human Rotavirus Vaccine in Finnish Infants

Abstract: RIX4414 strain of G1 human rotavirus vaccine was well-tolerated, immunogenic and efficacious in infants against rotavirus gastroenteritis during a 2-year period. To further increase vaccine "take" and efficacy, a higher dose of this vaccine may be considered for future efficacy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
2
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(114 citation statements)
references
References 20 publications
1
99
2
12
Order By: Relevance
“…6,8,18 For RV1, no difference versus placebo was observed in the incidence of diarrhea, fever or severe fever, vomiting or severe vomiting, and irritability or severe irritability within 14 days of immunization with any dose. 9,10,13,15 There was no statistically significant increased risk for death or other serious adverse events noted with either vaccine compared with placebo. Human strain 89-12 Composition Five human-bovine reassortant strains Single human strain RIX4414 G and P types G1P͓5͔ G1P͓8͔ G2P͓5͔ G3P͓5͔ G4P͓5͔ G6P͓8͔ Labeled indication Immunization against rotavirus gastroenteritis caused by G1, G2, G3, and G4 Immunization against rotavirus gastroenteritis caused by G1, G3, G4, and G9 Labeled age of administration, wk 6 through 32 11 Although neither RV5 nor RV1 has been associated with intussusception in large prelicensure trials, rigorous postlicensure monitoring for safety end points is necessary because of possible differences in the characteristics of infants receiving the vaccine in routine use compared with the clinical trials and the large numbers of infants being immunized.…”
Section: Reactogenicitymentioning
confidence: 91%
“…6,8,18 For RV1, no difference versus placebo was observed in the incidence of diarrhea, fever or severe fever, vomiting or severe vomiting, and irritability or severe irritability within 14 days of immunization with any dose. 9,10,13,15 There was no statistically significant increased risk for death or other serious adverse events noted with either vaccine compared with placebo. Human strain 89-12 Composition Five human-bovine reassortant strains Single human strain RIX4414 G and P types G1P͓5͔ G1P͓8͔ G2P͓5͔ G3P͓5͔ G4P͓5͔ G6P͓8͔ Labeled indication Immunization against rotavirus gastroenteritis caused by G1, G2, G3, and G4 Immunization against rotavirus gastroenteritis caused by G1, G3, G4, and G9 Labeled age of administration, wk 6 through 32 11 Although neither RV5 nor RV1 has been associated with intussusception in large prelicensure trials, rigorous postlicensure monitoring for safety end points is necessary because of possible differences in the characteristics of infants receiving the vaccine in routine use compared with the clinical trials and the large numbers of infants being immunized.…”
Section: Reactogenicitymentioning
confidence: 91%
“…Basados en la literatura se utilizó el valor de 85% de eficacia vacunal en la prevención de episodios graves de GE por RV, y de 85% para prevenir episodios de GE hospitalizados asociados con RV 19,20 . Se asumió que la vacuna tendría una eficacia de 85% para prevenir muertes por RV.…”
Section: A R T í C U L O D E I N V E S T I G a C I ó Nunclassified
“…Se asumió que la vacuna tendría una eficacia de 85% para prevenir muertes por RV. El 77,5% de eficacia calculado en la prevención de GE atendidos en consultas médicas se basó en un promedio entre la prevención de episodios graves (85%) 19,20 y episodios de cualquier gravedad (70%) 21 .…”
Section: A R T í C U L O D E I N V E S T I G a C I ó Nunclassified
“…This was followed by the licensing of an oral live attenuated two-dose rotavirus vaccine in 2008 (7,11,12). A randomized, double-blind, placebo-controlled trial showed vaccination to be 87% effective against rotavirus gastroenteritis in general, and 96% effective against severe gastroenteritis (10,13,14). In the United States, routine vaccination with rotavirus vaccine is estimated to prevent 40,000-60,000 hospitalizations each year (14)(15)(16).…”
Section: Preventing Disease With Life-saving Immunizationsmentioning
confidence: 99%